Understanding Environmental Tobacco Smoke and Influences for Smoking in Multiunit Housing - Dunlap, Christopher (My University, 2018)
This study explored some underlying reasons to why some smokers choose to smoke indoors as well as some of the factors that contributed to this decision. In addition, this study looked at what smokers know about environmental tobacco smoke (ETS) specifically in multiunit housing. This study primarily used a semi-structured interview to examine these areas as well other unexpected responses from these smokers. A final focus of this study was to see what smokers knew about thirdhand smoke, a form of ETS, and whether information about thirdhand smoke would affect their smoking habits. The results of this study showed that there many reasons as to why smokers choose to smoke indoors such as comfort and housing situation. In addition, many smokers did not know what thirdhand smoke was or what the health risks were when exposed to this form of tobacco byproduct.
Keywords: Health Promotion: Tobacco